“Noise Pollution, Effect of Noise on Behaviour of Animals and Human Health” - Syed Wahid Hasan; Dr. Md. Arshad Jamal (Zien Journals, 2021)
The paper deals with findings in animal’s response to noise. Noise pollution is a major problem in cities around the world. The noise from different normal and additionally manmade sources, particularly movement. Truth be told, commotion has come to be related with the physiological, physical, passionate and mental prosperity of an individual, but it people or even creatures. Factors including species, gender, age, and length of exposure on metabolism performance, health, reproduction, and behavior are discussed. Noise is defined as unwanted sounds in our communities except that which originates in the workplace. Effects of continuous and sudden noise on animals are also presented in detail. More physiological and behavioral responses have been described as increased hormonal production, increased heart rate, and reduction in production. Animal species exhibits a wide variety of responses to noise. Some animal species are more sensitive than others, because they may exhibit different forms or strengths of responses. Noise produces direct and cumulative adverse effects that impair health and that degrade residential, social and working environment with corresponding real (economic) and intangible (well–being) losses. Noise represents an important public health problem that can lead to hearing loss, sleep disruption, cardiovascular disease, social handicaps, reduced productivity, negative social behavior, annoyance reaction, absenteeism and accidents. Noise adversely affects general health and well-being in the same way as does chronic stress.
Keywords: Cardiovascular disease; hearing loss; annoyance